First record of the tropical aphid Schoutedenia ralumensis (Hemiptera, Aphididae) from Cambodia, with a re-description of the oviparous females and DNA barcoding - Hwalran Choi; Colin Favret; Seunghwan Lee (Biodiversity Data Journal)
Schoutedenia Rübsaamen, 1905 (Hemiptera, Aphididae, Greenideinae) is a small aphid genus associated with woody Euphorbiaceae and Phyllanthaceae. Of its two recognised species, Schoutedenia ralumensis Rübsaamen, 1905 is widely distributed across Southeast Asia, India, Africa and along the eastern coast of Australia. Taxonomic difficulties arise from subtle morphological differences and an unusual life cycle in which all morphs may occur simultaneously. Moreover, the oviparous female remains inadequately described, limiting reliable identification and comparative analyses.Schoutedenia ralumensis is newly recorded from Cambodia on Phyllanthus sp. (Phyllanthaceae). The poorly-known morphology of oviparous females is re-described with live photographs, biometric measurements and photomicrographic illustrations. Additionally, DNA barcoding, based on mitochondrial cytochrome c oxidase (COI) sequences, was performed on the Cambodian specimen and compared with available sequences, including one of S. emblica. Additionally, we propose the synonymisation of S. emblica under S. ralumensis as a conspecific variant. These findings expand the known distribution of S. ralumensis and contribute to a better understanding of aphid diversity in Cambodia.